2002
DOI: 10.1046/j.1365-2265.2002.01481.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations linked to familial hypokalaemic periodic paralysis in the calcium channel α1 subunit gene (Cav1·1) are not associated with thyrotoxic hypokalaemic periodic paralysis

Abstract: Mutations linked to familial hypokalaemic periodic paralysis in the calcium channel alpha1 subunit gene (Cav1.1) are not associated with thyrotoxic hypokalaemic periodic paralysis. However, polymorphisms in nucleotides 1551 and 1564 in the exon 11 were found in patients with familial hypokalaemic periodic paralysis and thyrotoxic hypokalaemic periodic paralysis in higher frequency than in controls. The polymorphisms identified within the Cav1.1 gene are associated with thyrotoxic hypokalaemic periodic paralysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 39 publications
2
32
1
9
Order By: Relevance
“…In view of the similarities between FHPP and TPP, such mutations have been examined in TPP patients. Most studies have demonstrated that none of the TPP patients carry the known mutations in CACNA1S, SCN4A, and KCNE3 genes [11,13,29,30]. In line with these studies, we did not detect the known defects in CACNA1S and KCNE3 genes, supporting the hypothesis that mutations in skeletal muscle ion channel genes associated with FHPP are not involved in the pathogenesis of TPP.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…In view of the similarities between FHPP and TPP, such mutations have been examined in TPP patients. Most studies have demonstrated that none of the TPP patients carry the known mutations in CACNA1S, SCN4A, and KCNE3 genes [11,13,29,30]. In line with these studies, we did not detect the known defects in CACNA1S and KCNE3 genes, supporting the hypothesis that mutations in skeletal muscle ion channel genes associated with FHPP are not involved in the pathogenesis of TPP.…”
Section: Discussionsupporting
confidence: 78%
“…Furthermore, it remains unclear whether the mutations in ion channel genes, if any, can explain the important clinical difference between FHPP and TPP, that is, TPP resolves completely following normalization of thyroid function. Whereas we did not find the polymorphism GGC/GGT at nucleotide 1551 nor the polymorphism CCC/CCT at nucleotide 1564 in the CACNA1S gene [11] in the present case, the significance of these polymorphisms remains to be determined. Since Na/K-ATPase activity is significantly higher in TPP patients than in uncomplicated thyrotoxicosis [31], its gene was analyzed in Chinese patients with TPP and no mutations were identified [31].…”
Section: Discussioncontrasting
confidence: 47%
See 2 more Smart Citations
“…Our group and others have demonstrated that mutations in the CACN1AS and SCN4A genes, present in familial forms of hypokalemic paralyses (FHypokPP), are not present in patients with TPP (11)(12)(13)(14). Kir2.x paralogues have constitutive thyroid hormone-responsive cis-elements (TREs) in their regulatory regions, therefore we screened the coding sequence of the KCNJ12 (Kir2.2), KCNJ4 (Kir2.3) and KCNJ14 (Kir2.4) genes.…”
Section: Thyrotoxic Hypokalemic Periodic Paralysis (Tpp)mentioning
confidence: 99%